OCHRATOXIN A, FUNGAL CONTAMINATION AND ANTIOXIDANT PROPERTY OF DEFECTIVE ARABICA COFFEE IN BENGUET, PHILIPPINES - Barcelo, Jonathan Mazon; Barcelo, Racquel Chua; Alvarez, Andrea (Emirates Journal of Food and Agriculture, 2017)
In Benguet, Philippines, efforts have been made to improve the production of high quality Arabica coffee beans (Coffea arabica). However, defects in coffee beans may still occur during post-harvest processing. Since defective coffee beans decrease the quality of coffee brews, they are commonly consumed in the municipality as beverage and are not sold commercially. In this study, the incidence of fungal and ochratoxin A contamination, in green and roasted immature and black defective coffee beans were investigated. Furthermore, the antioxidant properties of defective coffee beans were evaluated using a radical scavenging assay and metal chelating assay. It was found out that green coffee bean samples were contaminated with ochratoxigenic fungi and ochratoxin A. Roasting the green coffee bean samples decreased their total phenolic content, but increased their radical scavenging and metal chelating activities. The antioxidant activities, however, were statistically lower than standard antioxidants such as L-ascorbic acid, gallic acid and ethylene diamine tetraacetic acid (ρ<0.05). Ochratoxin A levels in defective green coffee beans also decreased after roasting. While phenolic compounds contribute to the antioxidant activities of the green coffee beans, the antioxidant activities of roasted coffee beans may be attributed to other antioxidant compounds formed during roasting. There is a need to further process contaminated defective coffee beans prior to utilization to isolate antioxidant compounds and remove ochratoxin A.